Highly Sensitive Ultraviolet Photodetectors Fabricated from ZnO Quantum Dots/Carbon Nanodots Hybrid Films - Guo, Deng-Yang; Shan, Chong-Xin; Qu, Song-Nan; Shen, De-Zhen (Scientific reports, 2014)
Ultraviolet photodetectors have been fabricated from ZnO quantum dots/carbon nanodots hybrid films and the introduction of carbon nanodots improves the performance of the photodetectors greatly. The photodetectors can be used to detect very weak ultraviolet signals (as low as 12 nW/cm 2 ). The detectivity and noise equivalent power of the photodetector can reach 3.1 × 10 17 cmHz 1/2 /W and 7.8 × 10 −20 W, respectively, both of which are the best values ever reported for ZnO-based photodetectors. The mechanism for the high sensitivity of the photodetectors has been attributed to the enhanced carrier-separation at the ZnO/C interface.